Pembelajaran Bahasa Kedua (Mandarin-HSK 3) Berbasis Mobile Learning - Miranti, Yang Nadia; Setyosari, Punaji; Ulfa, Saida (Universitas Negeri Malang, 2016)
Abstrak: Bahasa Mandarin sudah menjadi bahasa internasional kedua setelah Bahasa Inggris. Perkembangan bahasa Mandarin yang sangat pesat menjadikan pemerintah Tiongkok membuat standar tes bagi penutur bahasa Mandarin yang bukan penutur asli, tes ini dinamakan tes HSK (Hanyu Shuiping Kaoshi). HSK adalah tes kemampuan bahasa Mandarin yang berstandar internasional, yang terdiri dari level 1 sampai level 6, dan diselenggarakan oleh Dinas Pendidikan Tiongkok. Perkembangan teknologi memainkan peran penting bagi siswa yang memiliki kekhususan. Tujuan dari pengembangan ini adalah untuk mengakomodir kebutuhan siswa pembelajar bahasa kedua serta mengukur efektivitas penggunaan media dalam proses pembelajaran untuk mengetahui kelayakan produk pengembangan multimedia pembelajaran. Jenis penelitian adalah pengembangan mutimedia pembelajaran dengan model Lee & Owen. Subjek penelitian adalah siswa kelompok peminatan sastra mandarin fakultas ilmu budaya Universitas Brawijaya. Hasil pengembangan produk yaitu multimedia pembelajaran berbasis Mobile yang berisi materi Kosa Kata Hanyu Shuiping Kaoshi level 3 (HSK 3). Media yang dikembangkan dirancang sebagai media pembelajaran offline dan untuk mendapatkan software multimedia pembelajaran ini dapat diunduh di Play Store. Hasil Validasi ahli materi dan ahli desain media menunjukkan kriteria sangat layak. Hasil tanggapan siswa perorangan, kelompok kecil dan kelompok besar menunjukkan kriteria sangat efektif.Abstract: Mandarin has become the second international language after English. The rapid development of Mandarin language has made the Chinese government standardized tests for Chinese speakers who are not native speakers, this test is called the HSK test (Hanyu Shuiping Kaoshi). HSK is an international standard Chinese language proficiency test, which consists of level 1 to level 6, and is organized by the Chinese Education Service. Technological developments play an important role for students who have specificity. The purpose of this development is to accommodate the needs of students of second language learners and measure the effectiveness of media use in the learning process to determine the feasibility of learning multimedia development products. This type of research is the development of multimedia learning with the Lee & Owen model. The research subjects were students of the literary interest group of the UB Faculty of Cultural Sciences. The results of product development are Mobile-based multimedia learning to contain the Kosa word Hanyu Shuiping Kaoshi Level 3 (HSK 3) material. The developed media was designed as an offline learning media and to obtain multimedia learning software, it can be downloaded on the Play Store. The results of the validation of material experts and media design experts show that the criteria are very feasible. The results of responses of individual students, small groups and large groups showed very effective criteria.